Frequency and factors influencing men’s involvement in maternal care in tertiary care hospitals of Peshawar Pakistan - Ali , Mazhar; Qazi, Nadia; Ahmad, Mansoor; Qureshi, Masooma Khalid; Zakir, Marwa; Shah, Meraj Haider (International Journal of Pathology, 2024)
Background: Men’s involvement in maternal care positively affects maternal and infant health outcomes. This participation may include attending antenatal and postnatal visits, decision-making in pregnancy and childbirth, and providing emotional and financial support. This study aimed to determine the frequency of men’s involvement in maternal care and the factors influencing their engagement. Methods: A cross-sectional study was conducted from 13th March to 25th May 2023 at Hayat Abad Medical Complex and Northwest General Hospital, Peshawar. Data were collected through structured interviews with 246 women using a questionnaire. Responses were analyzed using SPSS version 21, ensuring accuracy and reliability. Results: The respondents had a mean number of children of 3.44. Among husbands, 93.9% were over 25 years old, and nearly half had at least an undergraduate education. A significant proportion of husbands participated in maternal care, with 76.7% attending antenatal visits, 53.5% present during labor, and 54.3% assisting with postnatal care. Factors identified as barriers included cultural norms (43.7%), socioeconomic issues (33.1%), and lack of supportive environments at hospitals (26.9%), and distance to healthcare facilities (39.2%). Increasing husband’s age correlated positively with postnatal support (Pearson coefficient: 0.266, p < 0.005) and was statistically significant for antenatal visits (p < 0.001) and postnatal care (p = 0.048), though not for attendance during labor (p = 0.198). Conclusion: Husbands demonstrated a high level of involvement in antenatal visits compared to labor and postnatal care. Most women reported satisfaction with their partner’s participation. While cultural norms, economic factors, and distance posed challenges, they did not majorly hinder involvement. Increased paternal involvement in maternal care should be encouraged to improve maternal and child health outcomes.